Antioxidant properties and phytochemical contents of Garcinia schomburgkiana Pierre - Imron Meechai (2018)
© 2016 Imron Meechai et al. This study was conducted to determine the phytochemical contents and radical scavenging activities of twelve Garcinia schomburgkiana extracts from the leaves, roots, twigs and branches. Among all extracts, the root (RA) and branch (BA) acetone extract revealed high phenolic (427.83±4.84 and 390.15±7.89 mg GAE/g extract), flavonoid (626.32±59.97 and 414.49±15.99 mg QE/g extract) and xanthone (625.80±3.78 and 615.07±9.97 mg AME/g extract) contents and possessed greater antioxidant capacities and radical scavenging activities than the standard vitamin C and Trolox. Our results reveal that G. schomburgkiana were potential natural sources of antioxidant with high amount of phenolics, flavonoids xanthones and beneficial fatty acid derivatives.